Policy and practice implication of - and tools to address - mental health and psychosocial support needs in Sierra Leone - Alastair Ager; Rebecca Horn; Abdulai Bah; Abdulai Bah; Haja Wurie; Mohamed Samai; Mohamed Samai (Frontiers in Psychiatry)
The last two decades have seen increased awareness of the impact of mental health issues on the population of Sierra Leone. Local capacity to respond to these needs is severely limited. In 2017, the Ministry of Health and Sanitation (MoHS) worked with staff of the College of Medicine and Allied Health Sciences (COMAHS – part of the University of Sierra Leone) and Queen Margaret University (QMU) in Edinburgh – and other stakeholders, including members of the Mental Health Coalition Sierra Leone – to define a research agenda that would support the development of community-based mental health and systems support in the community. This paper summarizes work over the course of the following six years in relation to this agenda, and indicates its relevance to ongoing and planned service developments. In terms of research advance, studies have – through participatory and ethnographically-informed methods – identified both local idioms and social determinants of distress and mapped health seeking pathways and barriers to care. This information was utilized in the development and validation of two culturally appropriate measures: the Sierra Leone Psychological Distress Scale (to assess mental health and psychosocial needs at the community level) and the Sierra Leone Perinatal Psychological Distress Scale (to identify common perinatal mental disorder in amongst pregnant and lactating mothers). For this latter population, a culturally adapted form of a problem solving intervention delivered through existing mother-to-mother supports has been shown to be feasible, acceptable and potentially effective. This work has major policy and practice implications, and early evidence of uptake is noted. This includes mental health capacity development through the online availability of training guides for the developed assessment scales and plans for incorporation of material regarding idioms and social determinants of distress in pre-and post-professional training curriculum. In terms of community-based initiatives, there has been evidence of uptake from the Mental Health Coalition Sierra Leone. In terms of policy, findings reinforce key principles regarding community-based provision, integration of mental health care into primary health care, and actions to reduce stigma associated with mental health.